1999
DOI: 10.1007/bf02482273
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and management of bronchogenic cysts: Report of 17 cases

Abstract: Between 1966 and 1996, 17 patients, comprising 1 child and 16 adults, underwent surgical treatment for bronchogenic cysts at the National Cancer Center Hospital. The bronchogenic cysts were located in the mediastinum in 11 patients and in the pulmonary parenchyma in 6. Of the 17 patients, 5 (29.4%) manifested symptoms, being more frequently seen in those with intrapulmonary cysts than in those with mediastinal cysts. Chest radiographs were ineffective for accurate preoperative diagnosis, but accurate diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 15 publications
2
50
0
5
Order By: Relevance
“…According to the literature, the preoperative CT diagnostic accuracy rate was 69.2%, while MRI diagnostic accuracy rate was 100%. 15) Therefore, McAdams et al suggested that CT is useful for initial evaluation of bronchogenic cysts, while MRI is needed for differentiation of high attenuation cysts from soft tissue masses. 4) In the past, we only knew that bronchogenic cysts occur most commonly in the lungs and mediastinum, but never experienced the cases with the cyst located outside of the parietal pleura in the chest cavity.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, the preoperative CT diagnostic accuracy rate was 69.2%, while MRI diagnostic accuracy rate was 100%. 15) Therefore, McAdams et al suggested that CT is useful for initial evaluation of bronchogenic cysts, while MRI is needed for differentiation of high attenuation cysts from soft tissue masses. 4) In the past, we only knew that bronchogenic cysts occur most commonly in the lungs and mediastinum, but never experienced the cases with the cyst located outside of the parietal pleura in the chest cavity.…”
Section: Discussionmentioning
confidence: 99%
“…However, to confi rm the cystic nature of a lesion based on HU, we considered lesions with values below 20 HU as cysts. In other cases magnetic resonance imaging can be used to identify bronchogenic cysts, and discriminate between solid and cystic masses, especially in cases with a high number of HU, giving an intense signal on T2-weighted MRI [12][13][14]. Alternatively, an EUS can usually distinguish between cystic and solid lesions, depending on location of the cyst in relation to the esophagus [9,15].…”
Section: Discussionmentioning
confidence: 99%
“…[9] A symptomatic bronchogenic cyst is an indication for surgical removal by either cyst excision or lobectomy by open thoracotomy or video assisted thoracic surgery (VATS). [10] There are controversies regarding whether an incidentally found bronchogenic cyst warrants operation or not, but as the course of these pathologies are unpredictable, several surgeons prefer preventive surgery. [10] …”
Section: Discussionmentioning
confidence: 99%